Forgery of Sale and Purchase Deeds on The Basis of Debt Receivables (Decision Study No. 10/Pid.B/2019/PN.Lbj) - Rahmadhani, Sylvia; Sembiring, Rosnidar; Mulyadi, Mahmud (Universitas Muhammadiyah Tangerang, 2025)
In the Indonesian legal system, debt agreements that transform into ownership transfers can create serious legal problems, particularly regarding potential document forgery crimes. Generally, this issue arises when creditors unilaterally create transfer deed documents for debt collateral objects without valid consent from debtors, especially when done through public officials such as PPAT (Land Deed Making Officer) in the form of Sale and Purchase Deeds. Based on this normative legal research which analyzes various aspects ranging from the formulation of document forgery crimes in the Criminal Code, the relationship between creating land sale and purchase deeds with forgery crimes, to judicial considerations in concrete cases, it was found that perpetrators of sale and purchase deed forgery can be sentenced to a maximum of 8 years imprisonment, and to prove the existence of forgery in deed creation requires strong evidence in court proceedings, as seen in Decision No. 10/Pid.B/2019/PN.Lbj which was ultimately declared time-barred due to exceeding the prosecution time limit